Doping w sporcie jako problem etyczno-społeczny = Doping in sport as a problem ethical and social - Lewandowska, Aleksandra; Leźnicki, Marcin (Journal of Education, Health and Sport, 2016)
Lewandowska Aleksandra, Leźnicki Marcin. Doping w sporcie jako problem etyczno-społeczny = Doping in sport as a problem ethical and social. Journal of Education, Health and Sport. 2016;6(7):548-555. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59006 http://ojs.ukw.edu.pl/index.php/johs/article/view/3719 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. DOPING W SPORCIE JAKO PROBLEM ETYCZNO-SPOŁECZNY DOPING IN SPORT AS A PROBLEM ETHICAL AND SOCIAL Aleksandra Lewandowska Katedra Studiów Miejskich i Rozwoju Regionalnego, Wydział Nauk o Ziemi Uniwersytet Mikołaja Kopernika w Toruniu lewandowska.aleksa@gmail.com Marcin Leźnicki Zakład Etyki, Wydział Humanistyczny Uniwersytet Mikołaja Kopernika w Toruniu lemahr@umk.pl Streszczenie: Celem pracy jest omówienie zagadnienia dopingu stosowanego w sporcie w kontekście prawdopodobnych konsekwencji społecznych związanych z jego stosowaniem, jak również na płaszczyźnie biomedycznej związanej z dynamicznym rozwojem technologii biomedycznych w obszarze wzmocnień ludzkiego organizmu. Poza analizą zagadnienia jakości „zdopingowanego sportu” w perspektywie rozstrzygnięć bioetycznych w tekście przywołane zostały statystyki ukazujące zastosowanie dopingu w sporcie, w ujęciu tak czasowym, jak również przestrzennym. Słowa kluczowe: sport, doping, doping genetyczny, etyka w sporcie, jakość w sporcie. Abstract: The article presents the issues of doping in sport used in the context of possible social consequences associated with its use, as well as at the level of biomedical related to the rapid development of biomedical technologies in area of human body enhancement. In addition to the analysis of quality issues "sport enhancement" in the perspective of bioethical resolving, in the text refers to statistics showing the use of doping in sport, in terms both time as well as spatial. Key words: sports, doping, gene doping, ethics in sport, quality in sport.